Is biliary lithiasis associated with pancreatographic changes?. Issue 5 (May 1995) - Barthet, M; Affriat, C; Bernard, J P; Berthezene, P; Dagorn, J C; Sahel, J
Abstract : The aetiological role of biliary lithiasis for chronic pancreatitis remains controversial. Previous studies based on pancreatographic studies reported changes in the pancreatic duct system caused by biliary lithiasis. This study analysed retrospectively the endoscopic retrograde cholangiopancreatography of 165 patients presenting with biliary lithiasis and of 53 controls. Among the 165 patients, 113 had choledochal stones (53 with gall bladder stones, 50 had had a cholecystectomy, 10 with a normal gall bladder), 35 had gall bladder stones without choledochal stones, 17 had cholecystectomy for gall bladder stones. Pancreatograms were analysed by measuring the diameter of the pancreatic duct in the head, the body, and the tail of the pancreas, and evaluating the regularity of the main pancreatic duct and the presence of stenosis, the regularity or the dilatation of secondary ducts, and the presence of cysts. In addition, we established a score, based on the above parameters, by which pancreatograms were classified as normal or with mild, intermediate, moderate or severe abnormalities. A multivariate analysis (stepwise multiple discriminant analysis) was performed for age, sex, presence of gall stones, presence of choledochal stones. Patients were comparable with controls for sex, alcohol consumption but were younger (55 v 68 years, p < 0.01). In patients and in controls, the frequency of pancreatographic abnormalities increased significantly with age. The pancreatographic features of patients and controls were not significantly different. In the multivariate analysis, age was the only factor with significant predicting value for pancreatographic abnormalities. In conclusion, biliary lithiasis in itself is not an aetiological factor for chronic pancreatitis, older age being responsible for the abnormalities seen by pancreatography of patients with biliary lithiasis.